2011
DOI: 10.5604/15093492.955725
|View full text |Cite
|
Sign up to set email alerts
|

Methods of Diagnosis and Treatment of Ankle Fractures - The Opinion of Members and Supporters of the Polish Foot and Ankle Society

Abstract: STRESZCZEnIEWstęp. Pra cę opar to na wy ni kach ba da nia an kie to we go prze pro wa dzo ne go wśród uczest ni ków III Kon gresu Pol skie go To wa rzy stwa Sto py i Sta wu Sko ko wo -Go le nio we go (Po lish Fo ot and An kle So cie ty -PF&AS), któ ry od był się w Ja star ni w dniach 22-24 kwiet nia 2010 ro ku.Ma te riał i me to dy. Wy ko rzy sta no opis kli nicz ny i ob raz ra dio lo gicz ny hi po te tycz ne go pa cjen ta, z ty po wym zła ma niem ko stek go le ni, aby okre ślić spo so by dia gno sty ki i le c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…[ 11 , 16 ] There is a rising demand for stress radiographs and less use of conventional radiographs in the current study (Table IV). [ 8 - 12 , 16 ] Although the decision of syndesmotic stability can be safely established with advanced radiological imaging studies such as ultrasound, computed tomography, and magnetic resonance imaging,[ 19 , 20 ] very few of the respondents reported using them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 11 , 16 ] There is a rising demand for stress radiographs and less use of conventional radiographs in the current study (Table IV). [ 8 - 12 , 16 ] Although the decision of syndesmotic stability can be safely established with advanced radiological imaging studies such as ultrasound, computed tomography, and magnetic resonance imaging,[ 19 , 20 ] very few of the respondents reported using them.…”
Section: Discussionmentioning
confidence: 99%
“…The combined use of the hook test and other intraoperative methods was similar to the findings of previous studies. [ 8 - 12 , 16 ] However, these results showed that Turkish orthopedic surgeons do not rely on the hook test alone as much as surgeons in the Netherlands. [ 9 ] Another interesting finding from the current survey was that 15.6% of the participants stated that they had already decided before surgery whether or not they would perform syndesmotic fixation.…”
Section: Discussionmentioning
confidence: 99%